2015
DOI: 10.1039/c4mb00265b
|View full text |Cite
|
Sign up to set email alerts
|

Systems analysis reveals down-regulation of a network of pro-survival miRNAs drives the apoptotic response in dilated cardiomyopathy

Abstract: Apoptosis is a hallmark of multiple etiologies of heart failure, including dilated cardiomyopathy. Since microRNAs are master regulators of cardiac development and key effectors of intracellular signaling, they represent novel candidates for understanding the mechanisms driving the increased dysfunction and loss of cardiomyocytes during cardiovascular disease progression. To determine the role of cardiac miRNAs in the apoptotic response, we used microarray technology to monitor miRNA levels in a validated muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 94 publications
(157 reference statements)
2
18
0
1
Order By: Relevance
“…The HF‐specific panel of seven circulating miRNAs identified in our study overlaps with published results of other related investigations. Although several investigators report an up‐regulation of miRNAs, more recent publications describe lower levels of miRNAs to be associated with cardiac disease, in concordance with our study . For example, a study of patients with symptomatic HF showed that 24 circulating miRNAs were decreased compared with control subjects, including miR‐26b‐5p, miR‐223‐3p, miR‐16‐5p, miR‐30e‐5p, miR‐423‐5p, miR‐27a‐3p, and miR‐18a‐5p, and Watson et al also found that all of the 5 identified circulating miRNAs were reduced in HF patients …”
Section: Discussionsupporting
confidence: 91%
“…The HF‐specific panel of seven circulating miRNAs identified in our study overlaps with published results of other related investigations. Although several investigators report an up‐regulation of miRNAs, more recent publications describe lower levels of miRNAs to be associated with cardiac disease, in concordance with our study . For example, a study of patients with symptomatic HF showed that 24 circulating miRNAs were decreased compared with control subjects, including miR‐26b‐5p, miR‐223‐3p, miR‐16‐5p, miR‐30e‐5p, miR‐423‐5p, miR‐27a‐3p, and miR‐18a‐5p, and Watson et al also found that all of the 5 identified circulating miRNAs were reduced in HF patients …”
Section: Discussionsupporting
confidence: 91%
“…A growing amount of evidence demonstrates that miRNAs can regulate apoptosis [ 38 ]. Thirteen miRNAs, including miR-21, were upregulated in early-stage dilated cardiomyopathy, whereas 11 miRNAs including miR-499 were downregulated [ 39 ]. MiR-499 was also downregulated in cardiomyocytes exposed to anoxia [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported quantitative changes in protein and cognate mRNA expression levels in cardiac ventricular tissue at different time points in the development of DCM in R9C-PLN mice representing clear clinical stages in the progression to HF (5). We showed that the latter maladaptive response was driven by elevated activity of MAPK signaling by the protein kinases p38 and JNK, in part through down-regulation of prosurvival microRNAs (6). However, the underlying upstream and downstream signaling events preceding HF were not fully explored.…”
Section: Phospholamban (Pln) Plays a Central Role In Camentioning
confidence: 99%